Sarcopenia and osteosarcopenia among patients undergoing hemodialysis - Xiang, Ting; Fu, Ping; Zhou, Li (Frontiers in Endocrinology, 2023)
Background: Sarcopenia and osteoporosis are closely interconnected and associated with adverse health outcomes. Osteosarcopenia is the concurrent presence of the two conditions and has rarely been reported in hemodialysis patients. Whether hemodialysis patients with osteosarcopenia are at greater risk of mortality than those with either condition alone remains unknown. The aim of this study was to explore the prevalence of sarcopenia and its association with osteoporosis and to determine its impact on survival risk in hemodialysis patients. Methods: A total of 209 adults undergoing hemodialysis were enrolled from the dialysis center in the West China Hospital of Sichuan University, and our study was registered at the Chinese Clinical Trial Register (number: ChiCTR2100043932). Muscle mass, handgrip strength, bone mineral density (BMD), and biochemical parameters were assessed. All deaths were recorded during a follow-up of 35.15 ± 15.37 months. Results: Seventy-eight patients were diagnosed with sarcopenia, with a prevalence of 37.3%. After adjustment for potential confounders, age (OR=1.094, P <0.001), female sex (OR= 3.44, P =0.005), diabetes (OR=3.756, P =0.008), CRP (OR=1.09, P =0.015), serum magnesium (OR=0.755, p=0.042) and BMI (OR=0.701, P <0.001) were independently associated with sarcopenia. Among the 209 patients, 103 patients completed the BMD assessment. The prevalence of osteosarcopenia was 22.3%, while 20.4% of participants had sarcopenia alone and 12.6% had osteoporosis alone. The proportions of patients who died were 13.0% for nonsarcopenia＆nonosteoporosis, 15.4% for osteoporosis alone, 47.6% for sarcopenia alone, and 52.2% for osteosarcopenia. Cox regression analysis showed that osteosarcopenia was independently associated with all-cause mortality (HR=3.74, 95% CI: 1.172-11.938), while osteoporosis alone and sarcopenia alone were not. Conclusion: Patients undergoing hemodialysis had a high incidence of sarcopenia and osteosarcopenia, muscle mass and strength showed a significant association with BMD, and osteosarcopenia might have a powerful impact on mortality in those patients.